DETEKSI PARASIT MALARIA PADA DARAH DONOR DI PALANG MERAH INDONESIA KABUPATEN ROKAN HILIR - Larisa, Vici; Lesmana, Suri Dwi; ", Fatmawati (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Malaria is one of the diseases caused by parasites and can cause death in humans. Malaria transmission can occur through blood transfusions. Incident of malaria transmission by transfussion increased especially in an endemic area. Rokan Hilir regency is an endemic area in Riau province so it has a high risk for transmission malaria by blood transfusions. This study is aimed to detection of malaria parasites in blood donors in Rokan Hilir regency. This is a descriptive study with cross sectional approached. The samples were 45 blood donors at Indonesian Red Cross Society Rokan Hilir regency and choiced by simple random sampling technique. The blood of donors are taken on scheduled blood donation those visited Indonesia Red Cross Society everyday. Detection of malaria parasites used RDT Inostics test kit and Giemsa stained thick and thin blood smear for microscopic examination. The frequency of malaria positive and frequency of malaria based on species of malaria parasites in blood donors at Indonesia Red Society Rokan Hilir regency was 0 (0%). It was conclude that there is no malaria parasite present in blood donors of Indonesian Red Society Rokan Hilir regency.Key words : malaria, malaria transmission by transfusion, blood of donors, malaria parasites detection, RDT, microscopis examination